Luminescence and scintillation properties of Gd3(Al5-xScx)O12:Ce garnet crystals grown by floating zone method. (July 2023) - Chewpraditkul, Warut; Kantuptim, Prom; Witkowski, Marcin E.; Makowski, Michał; Drozdowski, Winicjusz; Chewpraditkul, Weerapong; Yanagida, Takayuki
Abstract: The luminescence and scintillation properties of Ce 3+ -doped Gd3 (Al5-x Scx )O12 (x = 1, 1.5, 2, 2.5, 3) garnet crystals grown by the floating zone method were investigated. With increasing Sc content, the Ce 3+ 5d1 → 4f luminescence was blue shifted due to a decrease in 5d1 -5d2 crystal field splitting (Δ12 ) of the 5de doublet state. The Sc content showed a strong influence on purity of garnet phase in the Gd3 (Al5-x Scx )O12 :Ce crystals. The presence of secondary phase (perovskite and/or α-Al2 O3 ) results to a poor transparency and a lower light yield (LY) value. The Gd3 Al3 Sc2 O12 :Ce crystal exhibited pure garnet phase, highest quantum yield (∼76 %) and transmittance (∼80 %), and highest LY value (6, 850 photons/MeV at 662 keV γ rays) among the studied samples. Above RT, a decrease of radioluminescence (RL) yield occurs for all samples due to the thermal ionization process. A decrease of the RL yield at low temperature observed in correlation with the intense thermoluminescence peaks can be explained by the localization of electrons at intrinsic shallow traps. Highlights: Luminescence and scintillation characteristics of Gd3 (Al5-x Scx )O12 :Ce crystals are investigated. Temperature dependence of radioluminescence yield is measured in 10–350 K range. Gd3 Al3 Sc2 O12 :Ce shows highest quantum yield and light yield. Thermoluminescence and low-temperature afterglow are investigated.